Avoiding hemodynamic collapse during high‐risk percutaneous coronary intervention: Advanced hemodynamics of impella support - Verma, Sanjay; Burkhoff, Daniel; O'Neill, William W. (Catheterization and cardiovascular interventions, 2017)
The rate of performing primary percutaneous coronary intervention in patients with complex coronary artery disease is increasing. The use of percutaneous mechanical circulatory support devices provides critical periprocedural hemodynamic support. Mechanical support has increased the safety and efficacy of interventional procedures in this high‐risk patient population. Predicting patient response to the selected intervention can be clinically challenging. Here we demonstrate a case where complete hemodynamic collapse during PCI was avoided by mechanical support provided by the Impella device. Further, we employ a comprehensive cardiovascular model to predict ventricular function and patient hemodynamics in response to the procedure. New computational tools may help interventionists visualize, understand, and predict the multifaceted hemodynamic aspects of these high risk procedures in individual patients. © 2016 Wiley Periodicals, Inc.